2016
DOI: 10.1111/jog.12943
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of leiomyosarcoma localized in the Bartholin's gland area and review of the literature

Abstract: Sarcomas of the vulva in the Bartholin's gland area are extremely rare in adults and only a few cases have been reported in the literature. A 65-year-old female patient without any previous complaint presented to our hospital complaining of a genital lump with progressive enlargement over the last six months. Pelvic examination revealed a 6 × 5 cm solid mass lesion with irregular margins localized in the left Bartholin's gland. Preoperative pathology results indicated a benign lesion, which was subsequently to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…The literature review revealed only nine documented cases of leiomyosarcoma located in the Bartholin’s gland. 1 These cases commonly had an insidious course, presenting as enlarging painless solid mass located in the labia majora or minora. Other symptoms included pain, pruritus, and erythema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed only nine documented cases of leiomyosarcoma located in the Bartholin’s gland. 1 These cases commonly had an insidious course, presenting as enlarging painless solid mass located in the labia majora or minora. Other symptoms included pain, pruritus, and erythema.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomas account for 1% of all malignancies, while vulvar sarcomas account for 1–2% of vulvar tumors. 1 Leiomyosarcoma is the most common type of sarcoma presenting in the vulva and thought to originate from the smooth muscle within erectile tissue or the blood vessel wall, or in the erectile-pili muscle. Other rare vulvar sarcomas include epithelioid sarcoma, fibrosarcoma, hemangiosarcoma, malignant hemangiopericytoma, neurogenic sarcoma, dermatofibrosarcoma protuberans, and malignant fibrous histiocytoma.…”
Section: Introductionmentioning
confidence: 99%
“…Vereinzelt wurden größere Befunde vor Exzision gestanzt [9,10]. Kleinere nicht eindrückliche Befunde, unabhängig von der Lokalisation, können übersehen oder missinterpretiert werden.…”
Section: Diskussionunclassified
“…Sarcomas are tumors with mesenchymal origin and very poor prognosis compromising of 2% of all cancer deaths. These neoplasms are very rare and account for 1 to 2% of all malignancies (1)(2)(3)(4)(5)(6)(7). Sarcomas of the female genital tract have a low frequency of 3% (4,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Sarcomas of the female genital tract have a low frequency of 3% (4,8,9). In particular, vulvar sarcomas account for 1 to 2% of all the vulvar tumors, compared to the uterine sarcomas, which represent the vast majority of all sarcomas of the female reproductive system (90%) (2,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%